2017
DOI: 10.1007/s00170-017-0847-3
|View full text |Cite
|
Sign up to set email alerts
|

Injection molding simulation with solid semi-crystalline polymer mechanical behavior for ejection analysis

Abstract: Injection molded products, produced from semi-crystalline polymers may include undercut features which can introduce distortion to the shape of the product during ejection. A thermo-mechanical modeling approach for simulating these advanced ejection problems is developed. The approach is formed by combining a method for three-dimensional residual stress prediction and an advanced material model for modeling the solid visco-elastoplastic mechanical behavior. The task of this work is to assess, by analyzing a pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…About polymer fusion, different laws of viscoelasticity apply. This is an expression of the Maxwell model, the treatment of flow problems is based on the resolution of equations derived from conservation principles [16,17]: * Preservation of the mass:…”
Section: Finite Element Resolution Methodsmentioning
confidence: 99%
“…About polymer fusion, different laws of viscoelasticity apply. This is an expression of the Maxwell model, the treatment of flow problems is based on the resolution of equations derived from conservation principles [16,17]: * Preservation of the mass:…”
Section: Finite Element Resolution Methodsmentioning
confidence: 99%
“…The experimental counterpart of the examined case consists of pressure evolutions that were measured and published before [ 21 ]. The temperature of the mold cooling water was set to 50 °C, leading to about 52 °C at the surface of the cavity while the melt temperature was set to 220 °C.…”
Section: Methodsmentioning
confidence: 99%
“…For more details about the solver employed in this work, the reader is referred to Mole et al [8] and Krebelj and Turk [9].…”
Section: Numerical Discretizationmentioning
confidence: 99%
“…She also showed that differences in polymer and air viscosities were some of the main reasons for the large number of instabilities observed in the numerical calculation procedure. Recently, also aiming to model the IM process, the works in Mole et al [8] and Krebelj and Turk [9] implemented both the Cross-WLF and modified Tait models in the compressibleInterFoam (a solver designated by openInjMoldSim). The objective was to simulate the filling and packing stages, considering compressible flow, and applying appropriate models for the polymeric materials' behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation